Pengaruh Mentoring terhadap Identitas Diri Remaja Peserta Program Future Center Yayasan PESAT Cluster Kalimantan Barat - Tasuab, Irna Ireni; Santosa, Santosa; Tabrani, Ahmad (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Abstract: Mentoring is a process of trusting relationships in which the process of guidance, emotional support, goal achievement support, training, and teaching are included. This study aims to describe: adolescent self-identity, the mentoring process, and how strong the influence of mentoring on the development of adolescent self-identity. The study was conducted on 52 adolescents in the category of junior high school students participating in the Future Center program of the PESAT Foundation in the West Kalimantan cluster. The research method used is the quantitative research method. Data collection using questionnaires. The results of the first hypothesis research obtained a Lower Bound Interval confidence value of 58.32 and an Upper Bound Interval confidence value of 63.38, or the influence of mentoring in the strong category. The results of the second hypothesis test obtained a Lower Bound Interval confidence value of 40.27 and an Upper Bound Interval confidence value of 43.38, or it can be concluded that the self-identity of adolescents in the category is sufficient. The third hypothesis test obtained an r-value of 0.664 or in the strong category. Based on the results of the correlation coefficient, mentoring has a strong effect on adolescent self-identity. In the Model Summary table for R square (R²) of 0.441, which is then in percentage to 44.1%. This means that the percentage of the contribution of mentoring influence on the self-identity of adolescents participating in the Future Center program of the PESAT Foundation West Kalimantan cluster in the category of junior high school students is 44.1% and 55.9% is influenced by other variables. Mentoring has an important role in building adolescent identity. Therefore, it is necessary to equip mentors with knowledge and skills to assist youth participants in the Future Center program in West Kalimantan.Abstrak: Mentoring merupakan proses hubungan saling percaya yang di dalamnya termuat proses pembimbingan, pemberian dukungan emosional, dukungan pencapaian tujuan, pelatihan dan pengajaran. Penelitian ini bertujuan mendeskripsikan: identitas diri remaja, proses mentoring dan seberapa kuat pengaruh mentoring terhadap perkembangan identitas diri remaja. Penelitian dilakukan pada 52 remaja kategori pelajar SMP peserta program Future Center Yayasan PESAT di cluster Kalimantan Barat. Penelitian ini menggunakan metode kuantitatif. Pengumpulan data menggunakan kuesioner. Hasil penelitian hipotesis pertama diperoleh nilai convidedance Interval Lower Bound sebesar 58,32 dan nilai convidedance Interval Upper Bound sebesar 63,38, atau pengaruh mentoring pada kategori kuat. Hasil uji hipotesis kedua, diperoleh nilai convidedance Interval Lower Bound sebesar 40,27 dan nilai convidedance Interval Upper Bound sebesar 43,38, atau dapat disimpulkan bahwa identitas diri remaja pada kategori cukup. Uji hipotesis ketiga diperoleh nilai r sebesar 0,664, atau pada kategori kuat. Berdasarkan hasil koefisien korelasi maka mentoring berpengaruh kuat terhadap identitas diri remaja. Sedangkan pada tabel Model Summary untuk R square (R²) sebesar 0,441, yang kemudian di presentase menjadi 44,1%. Artinya bahwa presentase sumbangan pengaruh mentoring terhadap identitas diri remaja peserta program Future Center Yayasan PESAT cluster Kalimantan Barat kategori pelajar SMP sebesar 44,1% dan 55,9% dipengaruhi oleh variabel lain. Mentoring memiliki peran penting dalam membangun identas remaja. Oleh sebab itu, perlu memperlengkapi para mentor dengan pengetahuan dan keterampilan dalam mendampingi remaja peserta prgram Future Center di Kalimantan Barat